The Effect of Outside Temperature on Criminal Court Sentencing Decisions - Sally Evans; Peter Siminski (Institute of Labor Economics (IZA), 2020)
Climate change has stimulated growing interest in the influence of temperature on cognition, mood and decision making. This paper is the first investigation of the impact of temperature on the outcomes of criminal court cases. It is motivated by Heyes and Saberian (2019, AEJ: Applied Economics), who found strong effects of temperature on judges' decisions in immigration cases, drawing on 207,000 cases. We apply similar methods to analyse 2.8 million criminal court cases in the Australian state of New South Wales from 1994 to 2019. Most of the estimates are precise zeros. We conclude that outcomes of criminal court cases (which are far more prevalent globally than immigration cases) are not influenced by fluctuations in temperature, an unsurprising but reassuring result.
Keywords: K14; K41; Q54; 330; criminal courts; temperature; climate; decision making